Correlates with the distribution and abundance of endangered sclater’s monkeys (Cercopithecus sclateri) in Southern Nigeria (2007)
A distribution survey of the endangered Sclater’s monkey (Cercopithecus sclateri) was conducted over a wide area in southern Nigeria using forest surveys and hunter interviews. Sclater’s monkey, Nigeria’s only endemic primate species, is restricted to a land area of about 28,500 km2 in the densely human-populated, oil-producing region of southern Nigeria. Results indicate that this species is not as rare as previously thought; we confirmed its presence in 27 formerly unknown sites. Based on encounter-rate and distribution data, Sclater’s monkey is one of the two most abundant diurnal primate taxa across its range. However, the species primarily occupies isolated and degraded forest fragments. Although hunting is widespread, selective hunting of larger-bodied primate taxa offers some respite for the smaller Sclater’s monkey. We encountered this species more frequently in forests with relatively high hunting pressure, possibly indicating competitive release in the heavily hunted forests of southern Nigeria. Long-term persistence of Sclater’s monkey, which has no official protection throughout its range, depends on the willingness of hunters to target smaller-bodied wildlife (effortprofit trade-off), local bushmeat demand and protection of key forest fragments and the few larger forests in the region.